Analisis Akibat Hukum Perkawinan tanpa Kehadiran Wali Nikah Sesuai Hierarki ditinjau dari Perspektif UU Perkawinan dan Kompilasi Hukum Islam - Nathania Ratna Debriana; Soraya Firmansjah (Mahkamah : Jurnal Riset Ilmu Hukum, 2025)
Marriage is an important aspect of social and religious life, regulated by religious and state laws. This study aims to analyze the legal consequences of marriages that take place without the presence of a marriage guardian, especially in the context of a prospective bride whose status is a convert. From the perspective of Law No. 1 of 1974 concerning Marriage and the Compilation of Islamic Law, the presence of a marriage guardian is an absolute requirement for the validity of a marriage. This research uses a normative juridical method by utilizing literature studies as legal material to examine more deeply the hierarchy of marriage guardians and the implications arising from marriage without a marriage guardian. The results of this research show that a marriage that is not attended by a legal guardian can result in the invalidity of the marriage, which will have an impact on the legal status of children and women's rights. The case of Rizky Febian and Mahalini's marriage is a concrete example that shows the importance of the presence of a marriage guardian in maintaining the validity of marriage. This research is expected to provide a good understanding of the importance of marriage guardians and the legal procedures that must be followed in marriage, especially for prospective brides who convert to Islam.